Energising Fisheries Extension: Bridging Skills Gaps for Furthering Development in Haryana and Punjab - Naila M Bhat; Ananthan P.S.; Neha W. Qureshi; Shivaji D. Argade; Ponnusamy K.; Talib Mohammad (Journal of Indian Fisheries Association, 2023)
A well-prepared workforce is fundamental to the success of any extension organization. Given the rapid technological advancements, it’s crucial to continually enhance and refresh the skills of human resources. This study aims to recognize the training requirements of extension personnel within the State Fisheries Department (SFD) in the states of Haryana and Punjab. An organized questionnaire was integrated into an online survey and distributed to both headquarters and district departments. Besides descriptive statistics, the Weighted Sum Method was employed to evaluate training needs, with the scores being standardized. In terms of participation, fisheries district technical SFD staff from Haryana exhibited a 64% response rate, while Punjab recorded a 60% response rate. Gender distribution showed that about 43% of district technical staff in Punjab were female, while 11% in Haryana. Across both states, approximately 45% of the district technical staffs’ time was allocated to extension-related tasks. Notably, the primary training needs identified for SFD staff in Haryana included Better Management Practices (0.86), fish health management (0.83), and recent advancements in aquaculture technology (0.83). In Punjab, the top training needs for SFD staff encompassed fish nutrition and feed technology (0.85), fish health management (0.83), and recent technologies in aquaculture (0.83). Therefore, it is advisable to develop training programs aligned with these recognized needs to strengthen the extension system in both states.